Mechanisms of the influence of UV irradiation on collagen and collagen-ascorbic acid solutions - N. Metreveli; L. Namicheishvili; K. Jariashvili; G. Mrevlishvili; A. Sionkowska (International Journal of Photoenergy)
The study of the influence of UV irradiation on collagen solutions has shown the destabilization of the collagen molecule by calorimetric method. It is reflected both in changes of thermodynamic parameters of transition (Tm, ΔH, Cp=f(t)) and in the appearance of a low temperature peak, that is practically irreversible against rescanning. All these indicate that the important defects in the molecule occur. The ESR measurements have shown that the above-mentioned thermal changes are connected with the occurrence of free radicals in solution under UV irradiation. They interact with proline (Pro) residues of the protein with the appearance of secondary free radicals, with following migration to glycine (Gly) residues. The emergence of the free radicals at the Pro and then at the Gly residues may cause the dramatic structural defect resulting from the UV irradiation, which significantly alters the network of hydrogen bonds in the triple helix of the collagen molecule. All this is connected with destabilization of the collagen molecule, because the defects in amino acid residues probably lead to cleavage of covalent bonds near the damaged sites maintaining the triple helical structure. The presence of ascorbic acid in collagen solution protects the collagen molecule from occurring of secondary free radicals.